Performance analysis of three-phase hybrid fault current limiter with one commutation circuit. (December 2021) - Hamada, A.M.; Ghoneim, Sherif S.M.; Abdelwahab, Saad A. Mohamed; Abdellatif, Walid S.E.
Highlights: HCLID is a new current limiting means for one circuit commutation. The fault current commutation method is introduced as a new current limiting means. The HCLID consists of two electric circuits. Simulations and experimental results prove the feasibility of the new HCLID. Abstract: This paper describes the development of a hybrid fault current limiter and interrupting device (HCLID) suitable for low and medium voltage AC or DC industrial installations. By substituting the three-commutation circuit on each phase in HCLID with one controlled commutation circuit, the commutation capacitance, let-through current, volume, and weight can be reduced. Reducing the number of commutations circuit aims at decreasing the initial cost of the (HCLID), which is mainly the focus of the commutation capacitors. The fault current commutation method is introduced as a new current limiting means. This technique is based on the injection of counter-current to the main contacts of the circuit breaker for very fast-breaking of fault currents. The HCLID consists of two electric circuits, one to force the fault current down to zero (commutation circuit) and the other to establish the electro-dynamic force to separate the main contacts. The proposed control method is easy to implement and has a low initial cost. The simulated results presented in the research confirm the validity of the new HCLID over traditional methods. Experimental tests were carried out to validate the proposed method. Simulations and experimental results prove the feasibility of the new HCLID.